The heat equation on line with random right part from Orlicz space - Slyvka-Tylyshchak, A.I. (Carpathian Mathematical Publications, 2014)
In this paper, the heat equation with random right part is examined. In particular, we give conditions for existence with probability one of the solutions in the case when the right part is a random field, sample continuous with probability one from the Orlicz space. Estimation for the distribution of the supremum of solutions of such equations is found.